Guaranteed a posteriori error estimates for obstacle problem for elastic deformation of membrane - Harasim, P.; Szarkova, D.; Balko, L.; Valdman, Jan; Richtarikova, D. (Slovak University of Technology in Bratislava, 2015)
We apply functional a posteriori error estimate proposed by S. Repin for numerical solution of obstacle problem for membrane. Numerical solution of the obstacle problem is obtained by the finite element method using bilinear elements. Error of the approximation is estimated by a functional majorant. Thomas elements.
Keywords: A posteriori error estimate; Functional majorant; Obstacle problem